Psychological trauma, mood and social isolation do not explain elevated dissociation in functional neurological disorder (FND). (February 2023) - Blanco, S.R.; Mitra, S.; Howard, C.J.; Sumich, A.L.
Abstract: Functional Neurological Disorder (FND) results in altered motor, sensory and cognitive function in the absence of evident organic disease. It often co-occurs alongside dissociative disorders and dissociation has been found to be high in patients across FND subtypes (particularly in those with Non-Epileptic Attack Disorder; NEADs). However, the presence of dissociation in FND is varied and there are contradictory definitions and suggestions for elevated levels. Here, three studies show that dissociation is a prominent, defining feature of people with FND compared to those who are healthy or have other, similar long-term health conditions, and that this heightened dissociation is not explained by a history of trauma (study 1, N = 121), mood (study 2, N = 589) and is not associated with social isolation/social exclusion (study 3, N = 542). As dissociation appeared to occur in FND in the absence of the usual contributing factors, and as higher levels of dissociation were associated with increased disability and illness impacts, understanding its role is of fundamental importance to developing our understanding of FND. These findings have further applications, beyond the theoretical, in clinical settings and in research; the implications for further research are discussed. Highlights: Dissociation was found to be elevated in Functional Neurological Disorder. Dissociation is higher in those with FND compared to Healthy controls. FND participants report higher dissociation than other long-term conditions. Dissociation in FND appears unrelated to adverse life events, mood & social isolation. Increased levels of disability and anhedonia correlate with dissociation in FND.